Flexo-printed Busbarless Solar Cells for Multi-wire Interconnection. (November 2016) - Lorenz, A.; Gredy, C.; Senne, A.; Beyer, S.; Yao, Y.; Papet, P.; Ufheil, J.; Reinecke, H.; Clement, F.
Abstract: Flexographic printing is a high-throughput rotational relief printing method and represents a promising innovative approach for the front side metallization of silicon solar cells. The ability to realize narrow contact fingers with very low silver consumption makes this technology particularly interesting for busbarless solar cells with wire-interconnection like Meyer Burger's SmartWire Connection Technology (SWCT). This study intends to provide a comprehensive evaluation of the general feasibility for this approach. Fundamental printing tests are carried out to investigate important influence parameters like the flexible printing plate and the correlation between printing pressure and contact finger width. We found out that contact finger elements on elastomer printing plates down to an actual width of w f = 7 ± 2 μm can be realized using a high-resolution laser-engraving process. Furthermore, we show that printed contact finger width increases by approx. Δ w f ≈ 10 μm for each Δ p loc = 0.05 MPa of pressure increase and thus has a strong impact on the contact grid. Busbarless Al BSF Cz-Si solar cells with flexo-printed front side metallization are fabricated and measured using Pasan Grid TOUCH /Spot LIGHT -system. The best group of solar cells obtains a mean conversion efficiency of η = 19.0% and a maximum conversion efficiency of η max = 19.4%. A mini-module with the best two solar cells achieved a aperture conversion efficiency of η = 15.8%. Causes for cell-to-module losses are investigated and discussed in detail. In summary, we demonstrate the successful application of flexographic printing technology for the front side metallization of busbarless solar cells with multi-wire interconnection.